CONSUMER CONFIDENCE ON PURCHASE DECISION PROCESS ON THE KOSEEKER WEBSITE - Resty Aulia Damayanti (SOSCIED, 2022)
This study was conducted to determine the yield of the analysis of factors that influence the purchase decision of Koseeker in this study there is a phenomenon that there are consumers of Koseeker who are not satisfied with the consument confident, that has an impact on purchasing decisions. The technique that will be used in this research is sample random sampling, and probability sampling namely taking samples by setting specific characteristics that are in accordance with the research objectives so that it is expected to answer research problems. Based on the results of the descriptive analysis that has been enforce, it can be seen that the evaluation of respondents are in the high category, on statement trust to Koseeker for online payment a decimal score of 0,008, while the lowest respondent's response was costumer do purchase for twice statement regarding the Koseeker which obtained a decimal score of 0,0033.